A Turn-On Fluorescent Probe for Sensitive Detection of Cysteine in a Fully Aqueous Environment and in Living Cells - Xiaohua Ma; Guoguang Wu; Yuehua Zhao; Zibo Yuan; Yu Zhang; Ning Xia; Mengnan Yang; Lin Liu (Journal of Analytical Methods in Chemistry)
We reported here a turn-on fluorescent probe (1) for the detection of cysteine (Cys) by incorporating the recognition unit of 2,4-dinitrobenzenesulfonyl ester (DNBS) to a coumarin derivative. The structure of the obtained probe was confirmed by NMR and HRMS techniques. The probe shows a remarkable fluorescence off-on response (∼52-fold) by the reaction with Cys in 100% aqueous buffer. The sensing mechanism was verified by the HPLC test. Probe 1 also displays high selectivity towards Cys. The detection limit was calculated to be 23 nM. Moreover, cellular experiments demonstrated that the probe is highly biocompatible and can be used for monitoring intracellular Cys.